Pelatou : a Joker in the Neuro- anthropological Act - Ann, Appleton (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Pelatou is a traditional Melanau ritual carried out by a specialist a-bayoh (shaman) in the aftennath of a death. However, the multi-faceted nature of pelatou - part seance, part healing, part drama and entertainment, part play, part burlesque makes it difficult to categorize within the boundaries of other Melanau rituals and ceremonies concerned with death. The paper draws on Turner's concept of "play" (1987: 167-170) to analyse the nature and significance of what takes place in pelatou, and argues that it is the collective act of"perfonning" - rather than belief in the perfonnance itself - through which pelatou works its effect.